Femtosecond lasers in gas phase chemistry - Carley, R E; Heesel, E; Fielding, H H (Chemical Society reviews, 2005)
This critical review is intended to provide an overview of the state-of-the-art in femtosecond laser technology and recent applications in ultrafast gas phase chemical dynamics. Although "femtochemistry" is not a new subject, there have been some tremendous advances in experimental techniques during the last few years. Time-resolved photoelectron spectroscopy and ultrafast electron diffraction have enabled us to observe molecular dynamics through a wider window. Attosecond laser sources, which have so far only been exploited in atomic physics, have the potential to probe chemical dynamics on an even faster timescale and observe the motions of electrons. Huge progress in pulse shaping and pulse characterisation methodology is paving the way for exciting new advances in the field of coherent control.